Effect of pre-plant treatments of yam (Dioscorea rotundata) setts on the production of healthy seed yam, seed yam storage and consecutive ware tuber production - Abiodun Olufunmilayo Claudius-Cole; Lawrence Kenyon; Danny L. Coyne (Journal of Agriculture and Rural Development in the Tropics and Subtropics, 2017)
Numerous pests and diseases of yams are perpetuated from season to season through the use of infected seed material. Developing a system for generating healthy seed material would disrupt this disease cycle and reduce losses in field and storage. The use of various pre-plant treatments was evaluated in field experiments carried out at three sites in Nigeria. Yam tubers of four preferred local cultivars were cut into 100 g setts and treated with pesticide (fungicide + insecticide mixture), neem extract (1 : 5 w/v), hot water (20 min at 53 °C) or wood ash (farmers practice) and compared with untreated setts. Pesticide treated setts sprouted better than all other treatments and generally led to lower pest and disease damage of yam tubers. Pesticide treatment increased tuber yields over most treatments, depending on cultivar, but effectively doubled the production as compared to the control. Pesticide and hot water treated setts produced the healthiest seed yams, which had lower storage losses than tubers from other treatments. These pre-treated seed yams produced higher yields corresponding to 700 % potential gain compared to the farmers usual practice. Treatments had no obvious influence on virus incidence, although virus-symptomatic plants yielded significantly less than nonsymptomatic plants. This study demonstrated that pre-plant treatment of setts with pesticide is a simple and effective method that guarantees more, heavier and healthier seed yam tubers.